2007
DOI: 10.1128/jcm.01726-06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial Susceptibilities of Chlamydial Isolates from Western Barred Bandicoots

Abstract: A range of species of Chlamydiales have previously been detected in a variety of Australian marsupials, including koalas and western barred bandicoots. Thirty-seven ocular, urogenital, or nasal swabs were obtained from 21 wild western barred bandicoots. Chlamydia culture and antibiotic susceptibility testing were performed for cycloheximide-treated HEp-2 cells in 96-well microtiter plates. Chlamydia spp. were isolated from 11 specimens from 9 (42.8%) bandicoots. All isolates were identified as Chlamydiales by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…The C. pecorum susceptibility to enrofloxacin in this study was the same as that of C. pneumoniae isolated from western barred bandicoots (MIC 0.25–0.5 µg/mL); C. psittaci isolated from turkeys (MIC 0.25 µg/mL); and to the susceptibility of ruminant isolates of C. pecorum to other fluoroquinolones (ofloxacin MIC 0.25–0.5 µg/mL, ciprofloxacin MIC 0.25–1.0 µg/mL) . Additionally, C. pecorum susceptibility to chloramphenicol in vitro was similar to that of C. trachomatis isolated from humans (MIC 0.25–1.0 µg/mL; MIC 1.0 µg/mL; MIC 0.5–1.0 µg/mL), despite the lack of a standardised testing procedure for chlamydial susceptibility testing.…”
Section: Discussionsupporting
confidence: 66%
“…The C. pecorum susceptibility to enrofloxacin in this study was the same as that of C. pneumoniae isolated from western barred bandicoots (MIC 0.25–0.5 µg/mL); C. psittaci isolated from turkeys (MIC 0.25 µg/mL); and to the susceptibility of ruminant isolates of C. pecorum to other fluoroquinolones (ofloxacin MIC 0.25–0.5 µg/mL, ciprofloxacin MIC 0.25–1.0 µg/mL) . Additionally, C. pecorum susceptibility to chloramphenicol in vitro was similar to that of C. trachomatis isolated from humans (MIC 0.25–1.0 µg/mL; MIC 1.0 µg/mL; MIC 0.5–1.0 µg/mL), despite the lack of a standardised testing procedure for chlamydial susceptibility testing.…”
Section: Discussionsupporting
confidence: 66%
“…The in vitro susceptibility of koala isolates of C. pecorum and C. pneumoniae to enrofloxacin has not been determined. However, the MIC and minimum bactericidal concentration of enrofloxacin against C. pneumoniae isolated from another Australian marsupial, the western barred bandicoot, were both 0.25–0.5 mg/L (Kumar et al ., ), and the enrofloxacin MIC against Chlamydia psittaci isolated from turkeys was 0.25 mg/L (Butaye et al ., ). As the in vitro susceptibility of C. pecorum to antibacterials is similar across chlamydial species (Kumamoto et al ., ; Pudjiatmoko et al ., ), 0.25 mg/L was selected as the target MIC for antichlamydial dosing calculations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the route of infection from C. pneumoniae in the soil environment to humans is not easy to explain. C. pneumoniae infection has occurred in amphibians, koalas and horses; nevertheless, direct human infection from such species is unlikely (23,24,(27)(28)(29)(45)(46)(47)(48). Moreover, Bourke et al have reported a high prevalence of antibodies to C. pneumoniae in farmers in the United Kingdom (52), strongly implying that transmission may occur via a contagious source of C. pneumoniae in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…in vitro study has revealed that the survival of C. pneumoniae is increased in the presence of amoebae (22), although actual interaction in the field between C. pneumoniae and amoebae has not as yet been demonstrated. Other hosts that are naturally infected by C. pneumoniae include koalas, horses and free-ranging frogs, indicating that this bacterium is an important pathogen, infecting not only mammals but also amphibians, and that it may be widespread in natural environments (23)(24)(25)(26)(27)(28)(29). Other chlamydia, such as Parachlamydia acanthamoebae, which belongs to the order Chlamydiales, has been discovered to be the endosymbiont of acanthamoebae from the nasal mucosa of healthy volunteers, and to possess the ability to survive in natural environments (20,(30)(31)(32)(33).…”
mentioning
confidence: 99%